Factors Affecting SMEs in Bandar Lampung to Use Instagram Ads - Prasetyo, Adi; Rahmawati, Lilla; Paramitasari, Niken (Prosiding International conference on Information Technology and Business (ICITB), 2023)
This research aimed to determine the factors that influence SMEs in Bandar Lampung to advertise using the Instagram Ads feature. The population used in This research is about SMEs who have used the Instagram Ads feature with up to 100 samples were taken using the purposive sampling technique. The data analysis method in this study was the Cochran Q Test. The results of this research were 8 factors that influence SMEs in Bandar Lampung to advertise using features Instagram Ads. These factors are the influence of Instagram Ads on sales/revenue, there are default audience settings in Instagram Ads, Instagram Ads can be customized, Instagram Ads costs are cheap, there are audience settings Instagram Ads, audiences on Instagram Ads can be adjusted, settings on Instagram Ads is easy, and payment on Instagram Ads is easy. SMEs can use this factor as a reference for advertise on Instragram Ads or other platforms for digital marketing activities.Keywords— SMEs, Cochran Q Test, Instagram Ads, Digital Marketing